Blockchain Based Transactive Energy Market Using Peer-To-Peer(P2P) Energy Trading - Vasant U.S.; Shukla D.; Thakur A.K.; Singh S.P. (My University, 2025)
Energy trading through the use of peer to peer (P2P) approach is one of the challenging and yet developing approaches to implement a decentralized electricity market. In the transactive energy market, prosumers with an excess amount of energy behave as sellers and consumers with an energy deficit act as buyers. The platform proposed herein is basically an hour-ahead market, in which market subscribers, i.e., the peers of the market bid for trading of energy in the upcoming hour. Market clearing has been promulgated using P2P energy trading among consumers and producers, emphasizing privacy and security issues in the consumption and trading of electricity data using Blockchain technology. As the physical or distribution network is used for the transfer of energy, the power losses in the system are inevitable, and hence during P2P energy trading, grid usage costs are always encountered which are considered herein. The actual, specified, forecasted load profiles and the generation profiles are being used by each peer to bid in each hour. Network usage costs in the energy trading are calculated using a Subscription Charge (SC) algorithm; this charge is utilized as a price signal for reducing any chance of overload in the distribution network. To calculate SC, Power Transfer Distribution Factor (PTDF) concept is considered. The simulation is performed on IEEE 13 bus distribution network with ten consumers and two prosumers. Results obtained include the comparison of network subscribers in the presence of central authority as well as in its absence. © 2022 IEEE.